1971
DOI: 10.1071/ch9712389
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic hemiaminal formation in some N-unsubstituted azole aldehydes

Abstract: Cyclic hemiaminal formation in solid X-unsubstituted azole aldehydes seems to be a general phenomenon when stabilization factors and position of substitution are favourable. Previously reported for 5- substituted 1,2,4-triazole-3-carbaldehydes and benzimidazole-2- carbaldehyde, it has been found to occur also in some previously undescribed aldehydes of pyrazole, imidazole, 3H-imidazo[4,5- b]pyridine, 3H-imidazo[4,5-c]pyridine, and purine. In purine-8- carbaldehyde the hemiaminal may be accompanied by the aldeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0
1

Year Published

1972
1972
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…The 1 H NMR spectrum (CD 3 CN) of the reaction mixture obtained from propynal I and trimethylsilyl azide (III) contained signals belonging to triazole IV and a signal at δ 7.33 ppm (2H, d), which was assigned to CH proton in the pyrazine ring (monomerdimer ratio 1 : 1). In keeping with published data, signal from the CH(OH) fragment in cyclic hemiaminals derived from NH-azolecarbaldehydes is observed at δ 6.3-7.5 ppm [4]. Likewise, the 1 H NMR spectrum (CD 3 CN) of the reaction mixture obtained from propynal (II) and trimethylsilyl azide (III) contained signals from protons of triazole V, methine proton in the pyrazine ring of tricyclic hemiaminal VII at δ 6.46 ppm (2H, d), and methine proton in the triazole ring at δ 8.64 ppm (2H, d), the ratio monomerdimer being 1 : 1.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…The 1 H NMR spectrum (CD 3 CN) of the reaction mixture obtained from propynal I and trimethylsilyl azide (III) contained signals belonging to triazole IV and a signal at δ 7.33 ppm (2H, d), which was assigned to CH proton in the pyrazine ring (monomerdimer ratio 1 : 1). In keeping with published data, signal from the CH(OH) fragment in cyclic hemiaminals derived from NH-azolecarbaldehydes is observed at δ 6.3-7.5 ppm [4]. Likewise, the 1 H NMR spectrum (CD 3 CN) of the reaction mixture obtained from propynal (II) and trimethylsilyl azide (III) contained signals from protons of triazole V, methine proton in the pyrazine ring of tricyclic hemiaminal VII at δ 6.46 ppm (2H, d), and methine proton in the triazole ring at δ 8.64 ppm (2H, d), the ratio monomerdimer being 1 : 1.…”
supporting
confidence: 88%
“…Depending on the propynal structure, the reactions with methyl diazoacetate follow 1,3-dipolar cycloaddition pattern with formation of isomeric pyrazoles and products of dimerization of 5-formylpyrazoles to tricyclic bis-hemiaminals or/and aldol-like condensation to give α-diazo-β-hydroxyalkynes (in the absence of initiating species). It was also found that in the absence of a solvent 5-formylpyrazoles exist mainly as the corresponding dimers, 3,8-disubstituted dimethyl 4,9-dihydroxy-4H,9H-dipyrazolo[1,5-a:1',5'-d]pyrazine-2,7dicarboxylates, in a way similar to other fromylazoles (e.g., imidazoles and their fused derivatives and 1,2,4triazoles) in which the formyl group is attached to a carbon atom neighboring to the endocyclic NH group [4]. It should be noted that methyl 5-formyl-4-phenylpyrazole-3-carboxylate, unlike silicon-, germanium-, and alkyl-containing analogs, does not undergo dimerization under the same conditions [2].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Celle-ci peut ~tre obtenue notamment par la dim6-risation d'h&6rocycles azot6s porteurs d'un NH en d'une fonction ald6hydique (Browne, 1971). Cependant, l'6tude de ce type de fonction a 6t6 rendue difficile jusqu'& pr6sent par l'obtention de m61anges d'isom~res mal d6finis et par le fait d'un 6quilibre monom~re (ald6hyde)-dim~re (h6miaminal) en solution.…”
unclassified